2017
DOI: 10.1039/c6sc04456e
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the elimination of early and late transition metals: DFT mechanistic insights into the titanium-catalyzed synthesis of pyrroles from alkynes and diazenes

Abstract: A DFT study demonstrates that titanium is capable of promoting C–N bond formation via an unconventional reductive elimination pathway featuring back-donation (REBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 117 publications
0
33
1
Order By: Relevance
“…Previously, we computed the mechanisms of reaction (1) . For consistency, we adopted the same computational protocol in this study.…”
Section: Methodsmentioning
confidence: 85%
See 3 more Smart Citations
“…Previously, we computed the mechanisms of reaction (1) . For consistency, we adopted the same computational protocol in this study.…”
Section: Methodsmentioning
confidence: 85%
“…To release 3 a , the Ti−N and Ti−C δ covalent bonds of IM5 must break, which can be achieved by the oxidation of PhN=NPh through an interchange mechanism as represented by the formation of TS6 : PhN=NPh extracts one electron from each of the Ti−N and Ti−C δ bonds to form the two Ti−N bonds in IM6 , the remaining two electrons in the two covalent bonds forming the N=C π bond of 3 a . Previously, we have shown that IM6 can feasibly be converted into cat3 by disproportionation [reaction (3)] and we will not repeat these results in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This metallacycle then undergoes C-N reductive coupling to yield the product pyrrole and a Ti II fragment that is likely stabilized by backbonding 33 into the pyrrole 26 or an incoming diazene/alkyne 27 , in a manner similar to that seen for the Pauson-Khand reaction. Finally, reoxidation to a Ti imido via diazene disproportionation closes the catalytic cycle.…”
Section: C-n Bond Forming Reactionsmentioning
confidence: 90%